MULTIPLE TICKETING AS A PREDICTOR OF TRAFFIC VIOLATION AMONG COMMERCIAL MOTORISTS IN ENUGU STATE, NIGERIA - Ogunsakin, Alfred D. (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
There has been a growing concern about traffic violations among commercial transport operators in Nigeria. Although, studies in the past have implicated several factors in traffic behaviors. The present paper highlights the role of multiple ticketing in traffic violations among commercial motorists in Enugu state, Nigeria. One hundred and seventeen participants conveniently selected from different transportation hubs in Enugu urban responded to the study questionnaire. A cross-sectional survey design was adopted for the study. Data from the respondents were subjected to the statistical package for social sciences (SPSS, v17). A simple regression analysis was conducted to test the assumption that multiple ticketing will predict traffic violations among commercial motorists in Enugu State. The study revealed that multiple ticketing positively predicted traffic violation F (1,115), 36.71, P<.000. Notably, the R2 indicated that the independent variable contributed about 14.2% of the variation in traffic violations among the samples. The findings and recommendations are discussed.